Pengembangan Kawasan Wisata Pantai Bunga Indah Desa Kuhanga Kec. Bintauna, Kab. Bolaang Mongondow Utara dengan Menggunakan Pendekatan Arsitektur Tropis - Eka Y. Ramulya; Beby Sintia Dewi Banteng; Frans Mitran Ajami (Jurnal Ilmu Teknik Terapan, 2025)
As an archipelagic nation with the longest coastline in Southeast Asia, Indonesia holds immense potential for marine tourism. This sector plays a crucial role in economic development, especially in coastal regions. One such promising destination is Bunga Indah Beach in North Bolaang Mongondow Regency, North Sulawesi. Despite a significant increase in tourist visits, the development of this beach remains suboptimal, particularly concerning its infrastructure and planning. The existing facilities are self-built and poorly maintained, giving the area a neglected appearance. Another key issue is the lack of a design approach that is responsive to the tropical climate. Previous studies on coastal tourism development often focus solely on promotion or facilities, without integrating a tropical architectural approach that is adaptive to both the climate and local potential. Therefore, this study proposes the development of Bunga Indah Beach tourism area using a tropical architecture approach to create a space that is comfortable, sustainable, and harmonious with its environment. The analysis shows that implementing tropical architecture is an effective solution. The design of facilities such as accommodation, recreational areas, and educational spaces should consider functional, aesthetic, and environmental sustainability aspects. This approach not only enhances visitor comfort and energy efficiency but also strengthens the local architectural identity. Ultimately, this area is expected to become a major attraction that drives local economic growth while preserving ecological integrity.